Quantifying the effect of vortex generator installation on wind power production: An academia-industry case study. (December 2017) - Hwangbo, Hoon; Ding, Yu; Eisele, Oliver; Weinzierl, Guido; Lang, Ulrich; Pechlivanoglou, Georgios
Abstract: This paper presents an academia-industry joint study concerning effective methods to estimate and quantify the effect of vortex generator installation on wind power production. This problem has presented a challenge to the wind industry, because (a) vortex generator installation may lead to a moderate 1–5 % extra power production, but this level of improvement is difficult to be accurately detected; and (b) it is equally difficult to validate the estimated effect of vortex generator installation because a controlled experiment is practically impossible to conduct to provide a credible baseline. An academic institute and a wind technology company team up to tackle this challenge. The two teams develop their own version of quantification methods, which are profoundly different. The academic method uses 10-min data and makes use of both power and environmental data, whereas the company method uses high-frequency data via primarily a direct power comparison approach that relies less on the environmental data. When applying the respective methods to two inland wind farms, each of which presents four pairs of turbines, the quantification results from the two methods are surprisingly consistent. We believe the consistent outcome presents a strong case of cross validation, testifying to the respective method's capability and credibility. Highlights: This paper presents two methods for quantifying the effect of vortex generator installation on wind power production. The two methods yield consistent quantification results on eight pairs of turbines, located on two different wind farms. The consistent outcome presents a strong case of cross validation, testifying to the respective method's credibility. The methods introduced present the best alternatives to the standard IEC procedure for this quantification purpose.